Factors affect the adoption of mobile investment services in Malaysia - Liang, Pei Lin; Wee, Vincent Yong Jian (2023)
This study utilized the Technology Acceptance Model (TAM) to examine the factors that influence the acceptance of MIS in Malaysia. With the aim of achieving this goal, potential determinants that impact the inclination to embrace mobile investment apps were recognized and thoroughly assessed. Following the TAM framework, the variables considered PU, PEU, ATT, and an additional factor, PV. The participants in this investigation consisted of individuals aged 16 and above from Malaysia, resulting in 389 responses. Questionnaires were distributed to collect reliable primary data. The study formulated seven hypotheses to gauge the impact of these factors on Malaysians' adoption of mobile investment services. The subsequent sections encompass an exploration of the findings, implications for research, limitations, and recommendations. Hence, the main aim of this research was to explore the willingness of Malaysians to embrace the use of mobile investment services, providing valuable insights for researchers, developers of mobile investment services, and users.